Global Trade Pattern of Traditional Chinese Medicines and China's Trade Position - Xiang, Liyao; Chen, Zaoyu; Wei, Shaobin; Zhou, Haiyan (Frontiers in Public Health, 2022)
To depict the evolution of the global trade of traditional Chinese medicine (TCM) products, this paper analyzes the 2001-2020 trade data of TCM products in the World Bank and United Nations Commodity Trade Statistics Database to discern the spatial-temporal evolution characteristics of global and China’s trade patterns of TCM products from 2001 to 2020 and thereby assess the changes in the global trade of TCM products and in the positions of various countries/regions in the global trade of TCM products. Research findings are as follows: First, on the whole, the total trade volume of TCM products and number of participating economies and trade connections are on the rise. Second, in terms of topological structure, with higher network density and rising transmission efficiency, the global trade network of TCM products has typical small-world and scale-free network characteristics and has begun to be controlled by a few countries. Judging from the co-opetition between major trading countries, there are more diversified sources of imports for major trading countries and there is competition between supplying countries. Third, For China, the trade volume of TCM products between China and various countries worldwide has grown rapidly and exhibits a trend of continuous increase followed by decline. China has established extensive trade partnerships and its position in the global trade network of TCM products has been continuously improved. China’s participation has contributed to closer connection among trading entities, but its network heterogeneity remains to be further improved. From the perspective of trade interdependence, the number of countries/regions maintaining high interdependence with China has been gradually increasing and most of them are European and American countries, Japan and Southeast Asian countries. The number of countries/regions maintaining low interdependence with China has gradually decreased and countries/regions that are completely one-way dependent on China are nonexistent.